Pemberdayaan Masyarakat Dalam Pengentasan Stunting Di Jorong Sungai Talang - Sari, Wita Purnama; Fadila, Hana; Mulya, Sinta April; Ferza, Zilma; Neri, Refi Febria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This community service activity was motivated by low the participation of people at Jorong Sungai Talang to join social program that collage students of KKN PPM Terpadu Tuah Sakato 202 done there actively. People seen like uncare with the collage students that do KKN program there and people just focus on their activities. Because of that research about correlation between peoples’ background of work with their participation in any program at their village was needed. So the aim of this research was to find out the correlation between peoples’ background work with their participation to join the social program at their village. To get the answer of activity question of this activity used descriptive qualitative. Miles and Huberman model was technic analysis of the data used in this research. People around Jorong Sungai Talang were informant of this activity. The instrument use in this activity was observation, documentation and interview. This activity got several result. First the people at Jorong Sungai Talang just join the social program in cleanliness only. Then in any other social program they can not participation actively yet because their mindset which said that the day is the time to focus in garden.